STUDYING THE VOCABULARY OF THE MODERN RUSSIAN LANGUAGE OF THE XX AND XXI CENTURIES IN THE NATIONAL AUDIENCE - L. V. Polovina (Academia Science Repository, 2023)
Replenishment of the lexical stock of students, the development of the ability to correctly use words in speech and grammatically correctly formalize sentences is one of the tasks facing higher school teachers. The article is devoted to the study of the vocabulary of the modern Russian language in the national audience. The article discusses the peculiarities of studying the vocabulary of the XX and XXI centuries.